Randomized Pilot Study: Anal Inserts Versus Percutaneous Tibial Nerve Stimulation in Patients With Fecal Incontinence. Issue 4 (April 2021) - Leo, Cosimo Alex; Thomas, Gregory P.; Hodgkinson, Jonathan D.; Leeuwenburgh, Marjolein; Bradshaw, Ellie; Warusavitarne, Janindra; Murphy, Jamie; Vaizey, Carolynne J.
Abstract : BACKGROUND: Anal inserts and percutaneous tibial nerve stimulation may be offered to those with fecal incontinence in whom other conservative treatments have failed. OBJECTIVE: We aimed to compare anal inserts and percutaneous tibial nerve stimulation. DESIGN: This was an investigator-blinded randomized pilot study. SETTINGS: The study was conducted at a large tertiary care hospital. PATIENTS: Adult patients with passive or mixed fecal incontinence were recruited. INTERVENTIONS: Patients were randomly assigned to receive either the anal inserts or weekly percutaneous tibial nerve stimulation for a period of 3 months. MAIN OUTCOME MEASURES: The primary end point was a 50% reduction of episodes of fecal incontinence per week as calculated by a prospectively completed 2-week bowel diary. Secondary end points were St Mark's incontinence score, International Consultation on Incontinence Questionnaire-Bowel scores (for bowel pattern, bowel control, and quality of life), use of antidiarrheal agents, estimates of comfort and acceptability. RESULTS: Fifty patients were recruited: 25 were randomly assigned to anal inserts and 25 were randomly assigned to percutaneous tibial nerve stimulation. All completed treatment. A significant improvement of scores in the 2-week bowel diary, the St Mark's scores and the International Consultation on Incontinence Questionnaire-Bowel scores, was seen in both groups after 3 months of treatment. A reduction of ≥50% fecal incontinence episodes was reached by 76% (n = 19/25) by the anal insert group, compared with 48% (n = 12/25) of those in the percutaneous tibial nerve stimulation group ( p = 0.04). The St Mark's fecal incontinence scores and the International Consultation on Incontinence Questionnaire-Bowel scores for bowel pattern, bowel control, and quality of life ( p = 0.01) suggest similar improvement for each group. LIMITATIONS: A realistic sample size calculation could not be performed because of the paucity of objective prospective studies assessing the effect of the insert device and percutaneous tibial nerve stimulation. CONCLUSIONS: Both anal insert and percutaneous tibial nerve stimulation improved the symptoms of fecal incontinence after 3 months of treatment. The insert device appeared to be more effective than percutaneous tibial nerve stimulation. Larger studies are needed to investigate this further. See Video Abstract at http://links.lww.com/DCR/B460 . TRIAL REGISTRATION NUMBER: Clinicaltrials.gov No. NCT04273009. ESTUDIO PILOTO ALEATORIZADO DE INSERCIONES ANALES CONTRA LA ESTIMULACIÓN PERCUTÁNEA DEL NERVIO TIBIAL EN PACIENTES CON INCONTINENCIA FECAL: ANTECEDENTES: Las inserciones anales y la estimulación percutánea del nervio tibial (PTNS) se pueden ofrecer a las personas con incontinencia fecal que han fallado en otros tratamientos conservadores. OBJETIVO: Nuestro objetivo fue comparar inserciones anales y estimulación percutánea del nervio tibial. DISEÑO: Este fue un estudio piloto aleatorio ciego para investigadores. AJUSTE: El estudio se realizó en un hospital de atención terciaria. PACIENTES: Se reclutaron pacientes adultos con incontinencia fecal pasiva o mixta. INTERVENCIONES: Los pacientes fueron asignados al azar para recibir inserciones anales o estimulación del nervio tibial percutáneo semanal durante un período de tres meses. PRINCIPALES MEDIDAS DE RESULTADO: El principal resultado fue una reducción del 50% de los episodios de incontinencia fecal por semana, según lo calculado mediante un diario intestinal de dos semanas completado de forma prospectiva. Los criterios de valoración secundarios fueron la puntuación de incontinencia de St Mark, las puntuaciones del ICIQ-B (para patrón intestinal, control intestinal y calidad de vida), uso de agentes antidiarreicos, estimaciones de comodidad y aceptabilidad. RESULTADOS: Se reclutaron 50 pacientes: 25 fueron asignados al azar a inserciones anales y 25 a PTNS. Todo el tratamiento completado. Se observó una mejora significativa de las puntuaciones en el diario intestinal de dos semanas, la puntuación de St Mark y la puntuación del ICIQ-B en ambos grupos después de 3 meses de tratamiento. Se alcanzó una reducción de ≥ 50% de los episodios de incontinencia fecal en un 76% ( n = 19/25) en el grupo de inserción anal, en comparación con el 48% ( n = 12/25) de los del grupo de estimulación percutánea del nervio tibial ( p = 0, 04). Las puntuaciones de incontinencia fecal de St Mark, las puntuaciones del ICIQ-B para el patrón intestinal, el control intestinal y la calidad de vida ( p = 0, 01) sugieren una mejora similar para cada grupo. LIMITACIONES: No se pudo realizar un cálculo realista del tamaño de la muestra debido a la escasez de estudios prospectivos objetivos que evaluaran el efecto del dispositivo de inserción y la estimulación percutánea del nervio tibial. CONCLUSIONES: Tanto la inserción anal como la estimulación percutánea del nervio tibial mejoraron los síntomas de incontinencia fecal después de 3 meses de tratamiento. El dispositivo de inserción parecia ser más efectivo que la estimulación percutánea del nervio tibial. Se necesitan estudios más amplios para investigar esto más a fondo. Consulte Video Resumen en http://links.lww.com/DCR/B460 . NÚMERO DE REGISTRO DE PRUEBA: Clinicaltrials.gov No. NCT04273009.